Characterization of Cr3C2/Ni ceramic-metal composites produced by direct resistance rapid hot pressing method - Tunc, Buesra; Somunkiran, Ilyas; Balci, Esra (Springer Heidelberg, 2025)
The Cr3C2 phase of chromium carbides exhibits excellent corrosion resistance and low density, but vacancies in these materials sometimes limit their use in some applications. In order to expand the areas of use and further develop these materials, cermets containing metallic phases that provide better strength, hardness, and workability have been developed. This study examined the microstructure and mechanical properties of Cr3C2-Ni cermets fabricated through direct resistance rapid hot pressing. Cr3C2 and Ni powders were mixed in varying ratios, sintered, and analyzed using optical microscopy and X-ray diffraction for microstructural characterization. Mechanical properties were evaluated via Vickers hardness tests, density was measured using Archimedes' principle, and wear behavior was assessed. Results indicated that changes in Cr3C2 content significantly influenced mechanical properties and wear resistance, with the sample containing 18% Cr3C2 displaying superior strength and wear resistance. These findings highlight the potential of Cr3C2-Ni cermets in applications demanding robust and durable materials, representing a significant advancement in their development.
Keywords: High-Temperature Oxidation; Mechanical-Properties; Microstructure; Behavior; Cermets; Wear; Deformation; Performance; Cr3C2-Nicr; Evolution